Brazilian sharpshooters of the genus Homalodisca Stål, 1869 (Hemiptera, Cicadellidae): notes, new records, key to species, first description of the male of H. ignota Melichar, 1924, and a new Northeastern species - Takiya, Daniela M.; Cavichioli, Rodney R.; Mckamey, Stuart H. (Zootaxa, 2006)
Four species of the sharpshooter genus Homalodisca Stål are known to occur in Brazil: H. ignota Melichar; H. ignorata Melichar; H. lucernaria (Linnaeus), a senior synonym of the type-species Cicada triangularis Fabricius; and the new species H. spottii sp. nov. described from Bahia and Sergipe states. H. spottii sp. nov. is probably involved in the transmission of Citrus variegated chlorosis in Northeastern Brazil and is easily distinguished from other Homalodisca species by the (1) dark dorsum mottled with yellow; (2) contrasting yellow mesoscutellum; (3) broadly concave female sternite VII; and (4) aedeagal atrium not expanded dorsally and with 2 pairs of straight spiniform processes. Males and the female genitalia of H. ignota are described and illustrated for the first time (including an undistorted view of the female sternite VII). A sclerotized female internal sternite VIII in H. ignota and H. spottii sp. nov. is newly recorded for this genus. Homalodisca species are newly recorded for following Brazilian states: H. ignota from Rio de Janeiro and São Paulo; H. ignorata from Minas Gerais, Paraná, Rio de Janeiro, and Santa Catarina; and H. lucernaria from Pará and Roraima. A taxonomic key and notes on Brazilian species are also given.